2019
DOI: 10.3390/ijms20010183
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins and Bacteriophages: Therapeutic Weapons for Gastrointestinal Diseases?

Abstract: Bacteriocins are bactericidal peptides, ribosomally synthesized, with an inhibitory activity against diverse groups of undesirable microorganisms. Bacteriocins are produced by both gram-positive and gram-negative bacteria, and to a lesser extent by some archaea. Bacteriophages are viruses that are able to infect bacterial cells and force them to produce viral components, using a lytic or lysogenic cycle. They constitute a large community in the human gut called the phageome, the most abundant part of the gut v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 81 publications
0
71
0
9
Order By: Relevance
“…While the treatment of cystic fibrous (CF) patients with inhaled pyocins to elevate Pseudomonas colonisation or vaginally delivered colicins to treat E. coli UTIs may offer plausible options to control these common infectious diseases. Reports indicate, however, that pyocin did not control Pseudomonas lung infections in patients with cystic fibrosis despite promising in vitro findings [42]. Specifically, the findings of Ghoul et al show a lower bacteriocin diversity correlating with the ability of P. aeruginosa to persist in infections of the CF lung coupled with several immunity systems present in this species [43].…”
Section: Infectious Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…While the treatment of cystic fibrous (CF) patients with inhaled pyocins to elevate Pseudomonas colonisation or vaginally delivered colicins to treat E. coli UTIs may offer plausible options to control these common infectious diseases. Reports indicate, however, that pyocin did not control Pseudomonas lung infections in patients with cystic fibrosis despite promising in vitro findings [42]. Specifically, the findings of Ghoul et al show a lower bacteriocin diversity correlating with the ability of P. aeruginosa to persist in infections of the CF lung coupled with several immunity systems present in this species [43].…”
Section: Infectious Diseasementioning
confidence: 99%
“…Hertz et al report the in vitro anticancer activity of microcin E492 on colorectal and breast cancer cells at 5, 10, and 20 µg/mL via apoptosis and necrosis at concentrations of 10 and 20 µg/mL [47]. In vivo mice studies demonstrated the ability of nisin in controlling head and neck squamous cell carcinoma and oral cancer [42]. Notably, additional purified bacteriocins, including pyocin, colicin, pediocin, and microcin, have also displayed inhibitory properties against neoplastic cell lines and in xenograft mouse models [48].…”
Section: Anti-cancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of mechanisms and functions associated with the immunomodulatory effect of prebiotics have been reported, by the activation of genes and pathways implicated in immune processes [25]. It has been cited for many authors that the use of prebiotics in poultry diets improves bird's immunity through the selective growth of beneficial microbiota, resulting in an increased production of a variety of substances, such as bacteriocins and SCFA, that, in addition to being able to inhibit growth of pathogens, play a role in signaling pathway of immune system [97][98][99]. The chicken gut microbiota, especially Lactobacillus and Bifidobacterium, has also been reported to modulate intestinal gene expression, T cell-mediated immunity, and accelerated intestinal immune system maturation, by influencing the intestinal epithelium to produce antimicrobial peptides and cytokines such as IL-12, IFN-γ, IL-10, IL-1β, and TNF-α; modulating the immune system through enhancement of phagocytosis and proliferation of immune cells such as macrophages and monocytes; enhancing production of IgA, IgM, and IgG, reactive oxygen species, and reactive nitrogen species; and proliferating natural killer cells, CD3, CD4, and CD8 T cells [25,47,75,100].…”
Section: Enhancement Of Immune Systemmentioning
confidence: 99%
“…and we have exploited the requirement a → 0 as x → ∞ as per the boundary conditions (17) in order to derive the solution (23) in x > x 0 . We choose the peak of the sech 2 -pulse in (23) to be at x = x 0 + x R /m in order to simplify subsequent calculations.…”
Section: A Two-colony Solution With Immotile Bacteriamentioning
confidence: 99%